Analisis Suhu Permukaan Lahan Menggunakan Data Penginderaan Jauh Seri Waktu - Purnama, Syaiful Muflichin; Ningrum, Rheina; Karondia, Loryena Ayu; Putri, Caesarean Fadhilah (Departemen Teknik Geomatika ITS, 2024)
The research site is Tanjung Redeb Sub-district, Berau Regency, East Kalimantan. Tanjung Redeb Sub-district is experiencing a rapid urban development process. As a result, human demand for land use, especially built-up land, is increasing and affecting the amount of vegetation. The decreasing amount of vegetation leads to an increase in land surface temperature. The aim of this study is to determine the land surface temperature in the time series from 2014 to 2022 and to determine the relationship with changes in land cover. The analysis process is carried out using a remote sensing data approach through several extractions, namely the use of guided classification with random forest algorithms, NDVI (Normalised Difference Vegetation Index) and LST (Land Surface Temperature). The results of this study show that the land surface temperature of Tanjung Redeb District is dominated by temperatures of 21.4C-24.6C. While the results of the correlation test between vegetation index and land surface temperature obtained a value of -0.57154 (has a moderate relationship) with a correlation value marked (-) which shows the relationship that occurs in the opposite direction, the higher the vegetation index value, the lower the temperature and the R square (R2) of 0.417, the R2 value can prove that vegetation density has an influence of 41.7% on land surface temperature and the rest is influenced by other factors.